Pengaruh Influencer Marketing dan Electronic Word of Mouth Terhadap Minat Beli Konsumen Produk Skincare Glad2glow di Kota Bima - Wiwin Wiwin; Ismunandar; Ovriyadin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of influencer marketing and electronic word of mouth (e-WOM) on consumers' purchase intention toward Glad2Glow skincare products in Bima City. The research employed a quantitative approach with an associative design. Data were collected through questionnaires distributed to 96 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression supported by validity, reliability, and classical assumption tests. The findings indicate that influencer marketing has a positive and significant effect on purchase intention. Likewise, electronic word of mouth significantly influences consumers' purchase intention. Simultaneously, both variables have a significant effect on purchase intention, with a coefficient of determination of 73.7%, indicating that most variations in purchase intention are explained by influencer marketing and e-WOM. These findings suggest that effective influencer strategies and positive online consumer reviews play an important role in increasing consumers' interest in purchasing Glad2Glow skincare products. Future studies are recommended to include other variables, such as brand image, price, and product quality, to obtain a more comprehensive understanding of consumer purchase intention